Structure and mechanical properties of ultrafine-grained Ti-6Al-4V alloy made by applying reversible hydrogen alloying; Inorganic Materials: Applied Research; Vol. 4, iss. 2 - Grabovetskay G. P. Galina Petrovna; Stepanova E. N. Ekaterina Nikolaevna; Ratochka I. V. Iljya Vasiljevich; Naidenkin E. V. Evgeny Vladimirovich; Lykova O. N. Olga Nikolaevna (Materials For Aerospace Engineering, 2013)
Title screen